Meta‐analysis of the association of oestrogen receptor‐beta gene RsaI (G/A) and AluI (A/G) polymorphisms with male infertility. (23rd March 2014) - Cai, Y.; Liu, T.; Li, H.; Xiong, C.
Summary A more precise assessment of association of oestrogen receptor‐beta genes RsaI(G/A) and AluI(A/G) polymorphisms with male infertility from current contradictory results is the aim of this meta‐analysis including five RsaI and six AluI studies respectively. No association was observed between infertility and RsaI or AluI. In the stratified analysis by ethnicity, increased risk was found among Caucasians with GA versus GG (OR = 2.263, 95% CI = 1.073–4.776, I2 = 57.1%) and dominant model (OR = 2.117, 95% CI = 1.018–4.403, I2 = 49.0%) of RsaI. It was not observed for AluI. In the stratified analysis by infertility subtypes, a reduced risk in GA of AluI was observed among azoospermia or severe oligospermia (GA versus AA: OR = 0.686, 95% CI = 0.498–0.945, I2 = 21.2%; recessive model: OR = 1.403, 95% CI = 1.056–1.864, I2 = 31.7%), and reduced risk was in recessive model (OR = 0.650, 95% CI = 0.446–0.948, I2 = 0.0%) of subtypes, except for azoospermia or severe oligospermia. However, this finding was not observed in RsaI. The meta‐analysis showed GA and GG of AluI are possibly resistant factors for spermatogenesis dysfunction and deteriorated sperm quality.